Preliminary geophysical investigation in the archaeological site of Bocca delle Menate (Comacchio, FE). Issue 1 (1st April 2022) - Rizzo, E.; Dubbini, R.; Capozzoli, L.; De Martino, G.; Fornasari, G.; Farinatti, L.; Ferrari, E.; Clementi, J.; Romana Fiano, F.; Lombardi, M.
Abstract: The Bocca delle Menate archaeological site is located in Comacchio town (FE) and provides important evidence of the Roman presence in the Po Delta (Italy). The excavations realized sixty years ago have confirmed the presence of an extensive Roman villa and some part of it was highlighted. With the aim to identify the villa plan and the old highlighted archaeological remains, an archaeological preliminary survey and a geomagnetic geophysical campaign were carried out in October 2020. Although geophysical methods are now considered the best tools for archaeological detections, our results show that they are also excellent tools for the preservation, protection and monitoring of the excavated archaeological heritage.